1991
DOI: 10.1210/mend-5-11-1755
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Functional Properties of the A and B Forms of Human Progesterone Receptors Synthesized in a Baculovirus System

Abstract: Human progesterone receptors (PR) were overexpressed in Spodoptera frugiperda (Sf9) insect cells using a recombinant baculovirus system. Recombinant viruses were constructed that produced either full-length A (94K) or B (120K) forms of human PR, and each was expressed as a functional protein. Steroid and DNA binding activities were found to be indistinguishable from that of endogenous human PR in T47D breast cancer cells. Moreover, as analyzed by gel-mobility shift, recombinant PR-A and PR-B each bound to spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
3
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(75 citation statements)
references
References 51 publications
2
69
3
1
Order By: Relevance
“…As found previously when we purified endogenous T47D PR (20), alkaline elution of PR from antibody affinity resins is a relatively mild condition that retains the majority (60%) of the steroid originally bound to the native receptor (not shown). It should be noted that expression levels of PR in the present study are much higher (>10-fold) than the originally reported levels, which ranged between 0.1 and 0.2% of protein for expression of PR from these same baculovirus vectors (12). The higher levels of expression are due in part to inclusion of hormone which upregulates PR in Sf9 cells and to performing viral infection of insect cells as suspension rather than as attachment cultures (12).…”
Section: Methodscontrasting
confidence: 62%
See 1 more Smart Citation
“…As found previously when we purified endogenous T47D PR (20), alkaline elution of PR from antibody affinity resins is a relatively mild condition that retains the majority (60%) of the steroid originally bound to the native receptor (not shown). It should be noted that expression levels of PR in the present study are much higher (>10-fold) than the originally reported levels, which ranged between 0.1 and 0.2% of protein for expression of PR from these same baculovirus vectors (12). The higher levels of expression are due in part to inclusion of hormone which upregulates PR in Sf9 cells and to performing viral infection of insect cells as suspension rather than as attachment cultures (12).…”
Section: Methodscontrasting
confidence: 62%
“…PR-rich T47D human breast cancer cells and PR-negative MDA231 cells were cultured as previously described (19,20). Spodoptera frugiperda (Sf9) insect cells were grown at 27°C in Grace's insect medium (GIBCO) supplemented with 3.3 g of yeastolate (GIBCO) per liter, 3 (12,19,20).…”
Section: Methodsmentioning
confidence: 99%
“…PR-B was expressed in baculovirus-infected Sf9 insect cells as previously described (18). A detailed description of the PR-B purification and a quantitative analysis of its solution properties were also previously described (19).…”
Section: Expression and Purification Of The Full-length B-isoform Of mentioning
confidence: 99%
“…A general description of the different groups is given in the text. In group I, GR, MR, and PR are bound to HSP in the cytoplasm while estrogen receptor (ER), PR, and androgen receptor (AR) are reportedly bound to HSP in the nucleus (14,21,77). In group II, a ligand (stoichiometry not specified) may promote the association or dissociation of homo-and heterodimers in solution and on DNA depending on the ligand, the receptors, and the response elements involved.…”
Section: Vol 15 1995 Homodimerization Of Hnf-4 5139mentioning
confidence: 99%